Determination of Heavy Metals and Microbiological Contamination of Frozen Mackerel (Scomber scombrus) Sold in Eke-Awka Market, Awka, Anambra State, Nigeria (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
The determination of heavy metals and microbiological contamination of frozen mackerel fish (Scomber scombrus) sold in Eke-Awka market were carried out on five (5) randomly obtained samples with the codes; FOV (Frozen mackerel from vendor 1), FVT (Frozen mackerel from vendor 2), FTV (Frozen mackerel from vendor 3), FVF (Frozen mackerel from vendor 4) and FFV (Frozen mackerel from vendor 5). For the heavy metals analyses, concentrations of lead in the samples ranged from 0.00 to 4.00 x 10-3 mg/g. Apart from sample FFV which gave 0.00, all other samples showed lead contamination higher than Codex maximum limit of 0.3 x 10-3 mg/g. Mercury levels ranged from 0.10 to 0.40 x 10-3 mg/g, which were below the permissible guideline level of 0.5 x 10-3 mg/g as set by Codex for fish. This suggests that all the fish samples were well below permissible levels for mercury contamination. Chromium found in samples did not exceed the recommended daily intake. Arsenic and Cadmium were not detected in any of the samples. For microbiological analysis, the total heterotrophic bacterial count ranged from 1.0 x102 to 3.8 x 102 Cfu/g, total coliform count ranged from 1.4x102 to 2.5x 102 Cfu/g, total Salmonella count ranged from 1.0 x 102 to 1.2 x 102 Cfu/g, total Vibrio count ranged from 1.0 x 102 to 1.5 x 102 Cfu/g, and total fungal count ranged from 1.0 x 102 to 1.5x 102 Cfu/g. The study showed that the frozen mackerel fish samples were heavily contaminated with microorganisms, which may be attributed to their habitat, storage conditions and poor sanitary practices employed by the vendors.
Keywords: Frozen Mackerel; Heavy metals; Microbiological; Contamination